Zika Virus Targeting by Screening Inhibitors against NS2B/NS3 Protease. (22nd November 2019) - Choudhry, Hani; Alzahrani, Faisal A.; Hassan, Mohammed A.; Alghamdi, Asma; Abdulaal, Wesam H.; Bakhrebah, Muhammed A.; Zamzami, Mazin A.; Helmi, Nawal; Bokhari, Fawzi F.; Zeyadi, Mustafa; Baothman, Othman A.; Kamal, Mohammad A.; et al.
Abstract : Zika flavivirus is suspected to cause Guillain-Barre syndrome in adults and microcephaly, along with other congenital abnormalities in infants. Presently, no vaccines or therapeutics are available. Here, we report novel compounds identified by high-throughput virtual screening of Maybridge chemical database and molecular docking studies. We selected viral enzyme NS2B/NS3 serine protease as the therapeutic target because of its important role in viral replication. We selected seven potential compounds as antiviral drug candidates because of their high GOLD fitness score, high AutoDock Vina score, or X-Score binding energy and analyzed the strength of molecular interactions between the active site amino acids and selected compounds. Our study also provides a foundation for similar studies for the search of novel therapeutics against Zika virus.